Factors Influencing the Income of Micro, Small, and Medium Enterprises (MSMEs) in Minahasa Regency - Alzefin YRM Sinolungan; Rahel Widiawati Kimbal (International Journal of Applied Business and International Management, 2024)
This study investigates the factors influencing the income of Micro, Small, and Medium Enterprises (MSMEs) in Minahasa Regency. Specifically, it examines whether business capital, business location, training, and product promotion impact the income of these enterprises. The research encompasses 25 districts in Minahasa Regency and employs primary and secondary data, analyzed using multiple regression analysis. The independent variables include Capital (X1), Business Location (X2), Training (X3), and Promotion (X4), while the dependent variable is the income of MSMEs (Y). The objective is to determine the combined effect of business capital, location, training, and promotion on the income of MSEs in Minahasa Regency. The research findings indicate that capital, business location, training, and promotion significantly impact the income of MSME actors in Minahasa Regency. An adjusted R-square value of 0.648 suggests that these variables account for 64.80% of the income variation, while the remaining 35.20% is affected by other factors not considered in this model. Consequently, improving these factors can effectively increase the income of MSME actors in Minahasa Regency.